2020
DOI: 10.7554/elife.59600
|View full text |Cite
|
Sign up to set email alerts
|

Improving emotional-action control by targeting long-range phase-amplitude neuronal coupling

Abstract: Control over emotional action tendencies is essential for everyday interactions. This cognitive function fails occasionally during socially challenging situations, and systematically in social psychopathologies. We delivered dual-site phase-coupled brain stimulation to facilitate theta-gamma phase-amplitude coupling between frontal regions known to implement that form of control, while neuropsychologically healthy human male participants were challenged to control their automatic action tendencies in a social–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 72 publications
2
50
1
Order By: Relevance
“…This is, the increase of gamma activity during emotional action control was modulated by the PFC. Even more, in a transcranial alternating current stimulation (tACS) study, emotional control was elicited by increasing this PFC-M1 theta-gamma coupling ( Bramson et al, 2020 ). Other studies have characterized theta-gamma coupling and found that is modulated by sensory modulations.…”
Section: Motor Gamma Oscillationsmentioning
confidence: 99%
“…This is, the increase of gamma activity during emotional action control was modulated by the PFC. Even more, in a transcranial alternating current stimulation (tACS) study, emotional control was elicited by increasing this PFC-M1 theta-gamma coupling ( Bramson et al, 2020 ). Other studies have characterized theta-gamma coupling and found that is modulated by sensory modulations.…”
Section: Motor Gamma Oscillationsmentioning
confidence: 99%
“…In contrast to tACS, which uses a single-frequency stimulation (e.g., 10 Hz for alpha-band stimulation), NFB protocols usually train the whole bandwidth (e.g., the whole alpha bandwidth 8–13 Hz up). In multifrequency protocols, the NFB research field contains many studies using multifrequency protocols (Peniston and Kulkosky, 1991 ; Egner et al, 2002 ; Dohrmann et al, 2007 ; Friedrich et al, 2015 ; Vanneste et al, 2016 ; Güntensperger et al, 2019 ) whereas the multifrequency protocols in tACS seem to be quite an emerging field of research with a much shorter history than multifrequency NFB protocols (Helfrich et al, 2016 ; Lara et al, 2018 ; Bramson et al, 2020 ; Turi et al, 2020 ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…Despite the vast differences in mechanisms of action of tACS and NFB, according to the thorough research, both methods can successfully modulate various EEG bands (Lubar, 1997 ; Weber et al, 2011 ; Staufenbiel et al, 2014 ; Witkowski et al, 2016 ; Violante et al, 2017 ; Wischnewski and Schutter, 2017 ; Pimenta et al, 2018 ; Tseng et al, 2018 ; Abellaneda-Pérez et al, 2020 ). Both neuromodulatory methods have been also investigated in their ability to improve various brain functions such as motor performance (Joundi et al, 2012 ; Ros et al, 2014b ; Scharnowski et al, 2015 ; Moisa et al, 2016 ; Guerra et al, 2018 , 2019 ; Bologna et al, 2019 ), memory processes (Alexeeva et al, 2012 ; Polanía et al, 2012 ; Violante et al, 2017 ; Dobrakowski and Łebecka, 2020 ), attention (Escolano et al, 2014 ; Hopfinger et al, 2017 ; Berger and Davelaar, 2018 ; Deiber et al, 2020 ), creativity (Gruzelier, 2009 ; Agnoli et al, 2018 ; Di Bernardi Luft et al, 2018 ), emotional regulation (Johnston et al, 2010 ; Bramson et al, 2020 ), etc. (Hohn et al, 2019 ; Prim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that decreased resting-state theta–gamma PAC may be a biomarker of poorer mental health (specifically depression) and that lasting changes in PAC may be a mechanism underlying TMS treatment. Notably, cross-frequency theta–gamma tACS protocols have been demonstrated to influence memory ( Alekseichuk et al, 2016 ; Lara et al, 2018 ), cognitive control ( Turi et al, 2020 ), and emotional-action control ( Bramson et al, 2020 ). Alekseichuk et al (2016) reported that theta–gamma tACS has a greater effect on working memory than theta tACS.…”
Section: Pac Neurostimulation and Mental Healthmentioning
confidence: 99%